Families and friends group: a group that straddles teaching, support and transformation. (September 2019) - Radcliffe, Michelle; Cilasun, Jale
This article describes the structure, process and evaluation of a families and friends group in a personality disorder treatment service for people experiencing Borderline Personality Disorder using a Mentalization Based Therapy model. We highlight the benefits of working with family members and consider the differences between psycho-education, support groups and group-analytical approaches. Inclusion of families in recovery is well argued. Providing support and education for family members can improve communication and reduce burden in families. In the treatment of patients with Borderline Personality Disorder, the focus often remains upon meeting patients' needs and not of those who support them. We used a formal evaluation of the effectiveness of the families and friends group in the areas of learning and support. Qualitative questions were used to gain more in depth information regarding the impact of the group. Our results support the approach of working with the family rather than only focusing on the individual. There was an improvement in the communication leading to positive change in relationships between family members and their loved ones. This takes place despite the group being a once a month and drop-in. However, as this was evaluation of one service, more research in this area is needed.